Era Baru Indonesia: Sosialisasi Pemikiran Amin Rais, Hamzah Haz, Motori Abdul Djalil, Nur Mahmudi, Yusril Ihza Mahendra Cet. 1 Novianto, Kholid, - Novianto, Kholid; Al Chaidar (Raja Grafindo Persada, 1999)
173 hlm.; 25 cm.